Method for modelling of fluxgate sensor including the geometry influence. Issue 4 (1st July 2014) - Li, Juping; Liu, Shibin; Guo, Bo; Hou, Xiaowei; Yang, Shanglin; Qiu, Songsong
Abstract : This study proposes a new method of SPICE modelling of fluxgate sensor that considers the geometry of the fluxgate. The main advantage of the method, vis‐a‐vis the traditional model using demagnetisation factor, is that the inhomogeneity of the magnetisation is taken into consideration. The parameters including magnetic performance of core, the geometry of the fluxgate can be regulated easily. The proposed method was tested for a rod shape core fluxgate, showing a good agreement with experiment results.